2023
DOI: 10.1007/s43452-023-00700-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pulsed electric current on the structural and mechanical behavior of 6016 aluminium alloy in different states of hardening

Abstract: This study presents the effect of high current pulses on the structural and mechanical behavior of the 6016 aluminium alloy in three different states of hardening: naturally aged, super saturated, and annealed. The 6016 aluminium alloy was used for the first time in terms of electrically-assisted forming. The influence of the application of different current parameters on the material behavior was conducted. The study of electrically-assisted tensile tests showed that the application of current pulses results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Thus, paper [ 54 ] shows the possibility of additional structure refinement due to the particle formation. Work [ 42 ] describes the structural changes in 6016 aluminum alloy in various initial states (quenched, annealed, and naturally aged) during tension with and without current. The authors noted brittle intergranular fracture in all states; however, they observed some differences in fracture for specimens under tension with and without current ( Figure 12 ).…”
Section: Microstructure Featuresmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, paper [ 54 ] shows the possibility of additional structure refinement due to the particle formation. Work [ 42 ] describes the structural changes in 6016 aluminum alloy in various initial states (quenched, annealed, and naturally aged) during tension with and without current. The authors noted brittle intergranular fracture in all states; however, they observed some differences in fracture for specimens under tension with and without current ( Figure 12 ).…”
Section: Microstructure Featuresmentioning
confidence: 99%
“…However, some researchers note a decrease in plasticity under the action of current, but these effects are found in alloys disposed to aging [ 42 ]. The microhardness ( Figure 13 a) of naturally aged 6016 aluminum alloy was reduced by a combination of rolling and current.…”
Section: Physical–mechanical and Technological Propertiesmentioning
confidence: 99%
See 3 more Smart Citations